AAGBS welcomes Dаtо' Моhamed Rafique Merican as Adjunct Professor - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
We are delighted to announce the appointment of Dato' Mohamed Rafique Merican Mohd Wahiduddin Merican as an Adjunct Professor at the Arshad Ayub Graduate Business School (AAGBS). Effective 15 March 2024, this appointment marks a significant milestone as our academic community continues to grow in strength, wisdom, and industry-driven expertise. Dato' Mohamed Rafique's extensive professional experience and leadership insights will bring invaluable perspectives to AAGBS, enriching teaching, learning, and knowledge exchange between academia and industry. His presence reflects AAGBS' commitment to academic excellence, practical relevance, and the cultivation of future-ready business leaders.